A Top-down Approach to S-UTD-CH Model - Mehmet B. Tabakcioglu (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Free space electromagnetic wave propagation is an excessively pretty simple. However, in the reality, there are obstructions like buildings and hills blocking the electromagnetic waves and leading diffraction and reflection, and these obstructions can be modeled as a knife edge or wedge due to using of UHF. Hence, the vital problem is how an electromagnetic wave propagates in multiple diffraction scenario including buildings, trees, hills, cars etc. In order to estimate the field strength or relative path loss of the waves at the receiver, so many electromagnetic wave propagation models have been introduced throughout the century. Ray tracing and numerical integration based propagation models are introduced. In this paper, detailed information is provided about S-UTD-CH (Slope UTD with Convex Hull) model. Particularly, in the transition zone, the S-UTD-CH model can be applied to multiple diffraction scenarios. In addition, Fresnel zone concept, convex hull and slope UTD models are fundamentals of the S-UTD-CH model. Moreover, in terms of computation time and accuracy, the S-UTD-CH model is conceived an optimum model. Furthermore, verification of S-UTD-CH model is made by means of FEKO, which is a comprehensive electromagnetic simulation software tool by Altair.